HOME REVIEW PROGRAM IN THE INTEREST OF POVERTY REDUCTION: TOWARDS SUCCESS OR THE VERSE? - Rosa Amelia Sukma; Harry Priyanto; Herwin Kurniadi (RADJA PUBLIKA, 2023)
Implementation of the house renovation program by the Temuasri Village Government so that the houses of the poor who are uninhabitable become livable. In this way, order, stability, peace and prosperity will be realized in society. Even though it has a positive impact, the reality of limited government budgets so that the community has to bear the remaining budget needed is a serious problem in implementing the house renovation program. Objectives: To describe, analyze, and interpret the implementation of the house renovation program in the context of poverty alleviation in Temuasri Village. Method: Using qualitative principles according to constructive and participatory models. Primary data from interviews, and secondary data from the results of literature studies and various regulations relevant to the substance of the research. Results: Move quickly to implement the house renovation program to provide livable housing for low-income people, equitable development as well as improving the quality of life. Conclusion: The success of poverty alleviation should not be measured only from the physical aspect of the house, but from the economic, educational and health aspects. If one of the conditions for government assistance to the poor is that the condition of the house is uninhabitable, then receiving a house renovation program is akin to deepening the poverty gap.